1986
DOI: 10.1038/jcbfm.1986.106
|View full text |Cite
|
Sign up to set email alerts
|

Subarachnoid Hemorrhage in the Rat: Cerebral Blood Flow and Glucose Metabolism during the Late Phase of Cerebral Vasospasm

Abstract: Summary: A double-isotope technique for the simulta neous measurement of CBF and CMRglu was applied to a subarachnoid hemorrhage (SAH) model in the rat. Cis ternal injection of 0.07 ml blood caused a rather uniform 20% reduction in CBF together with an increase in glu cose utilization of 30% during the late phase of vaso spasm. In one-third of the SAH animals, there were focal areas where the flow was lowered to 30% of the control values and the glucose uptake increased to �250% of control. We suggest that blo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
24
0
1

Year Published

1988
1988
2007
2007

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(27 citation statements)
references
References 52 publications
2
24
0
1
Order By: Relevance
“…Considerable clinical and experimental work has shown that SAH induces focal and generalized disturbances of several brain functions, such as reduced cerebral blood flow (d'Avella et al, 1996;Delgado et al, 1986;Jackowski et al, 1990;Prunnel et al, 2003Prunnel et al, , 2004, impaired control of vascular autoregulation Delgado et al, 1985;Sasaki et al, 1982, 1985), BBB dysfunction (d'Avella et al, 1994Doczi et al, 1985Doczi et al, , 1986Germanò et al, 1992Germanò et al, , 1998bGermanò et al, , 2000Germanò et al, , 2002Gules et al, 2003;Imperatore et al, 2000;Zuccarello et al, 1989), brain edema and increased intracranial pressure (ICP) (Jackowski et al, 1990), and free-radical generation associated with lipid peroxidation phenomena (d'Avella et al, 1990Doczi, 1985;Doczi et 1986; Enblad et al, 1996;Germanò et al, 1992Germanò et al, , 1998bGermanò et al, , 2000Germanò et al, , 2002Imperatore et al, 2000;Jackowski et al, 1990;Kawamata et al, 1997;Koide et al, 1985;Nilsson et al, 1996Nilsson et al, , 1999Persson et al, 1996;Siesjo et al, 1992a,b;Smith et al, 1996;Staub et al, 2000;Yoshida et al, 1980;Zuccarello et al, 1989).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Considerable clinical and experimental work has shown that SAH induces focal and generalized disturbances of several brain functions, such as reduced cerebral blood flow (d'Avella et al, 1996;Delgado et al, 1986;Jackowski et al, 1990;Prunnel et al, 2003Prunnel et al, , 2004, impaired control of vascular autoregulation Delgado et al, 1985;Sasaki et al, 1982, 1985), BBB dysfunction (d'Avella et al, 1994Doczi et al, 1985Doczi et al, , 1986Germanò et al, 1992Germanò et al, , 1998bGermanò et al, , 2000Germanò et al, , 2002Gules et al, 2003;Imperatore et al, 2000;Zuccarello et al, 1989), brain edema and increased intracranial pressure (ICP) (Jackowski et al, 1990), and free-radical generation associated with lipid peroxidation phenomena (d'Avella et al, 1990Doczi, 1985;Doczi et 1986; Enblad et al, 1996;Germanò et al, 1992Germanò et al, , 1998bGermanò et al, , 2000Germanò et al, , 2002Imperatore et al, 2000;Jackowski et al, 1990;Kawamata et al, 1997;Koide et al, 1985;Nilsson et al, 1996Nilsson et al, , 1999Persson et al, 1996;Siesjo et al, 1992a,b;Smith et al, 1996;Staub et al, 2000;Yoshida et al, 1980;Zuccarello et al, 1989).…”
Section: Discussionmentioning
confidence: 99%
“…These impairments have been ascribed mainly to ischemic brain injury occurring either during the initial bleeding episode or as a consequence of macro-and microvascular dysfunction and delayed ischemic deterioration (d'Avella et al, , 1996Delgado et al, 1985Delgado et al, , 1986Doczi, 1985;Doczi et al, 1986;Germanò et al, 1992Germanò et al, , 2000Jackowski et al, 1990;Johshita et al, 1990;Sasaki et al, 1985Sasaki et al, , 1986Siesjo, 1992a,b;Zuccarello, 1989). Detailed knowledge about the pathological ischemic mechanisms in patients with SAH is critical to develop more efficient treatments.…”
Section: Introduction Dmentioning
confidence: 99%
“…Our current knowledge of experimental subarachnoid hemorrhage in rat models is mostly limited to the singlehemorrhage model (11,12,19). Only recently have the double-hemorrhage model (30,44) or endovascular puncture model (38) been reported on.…”
Section: Discussionmentioning
confidence: 99%
“…A substantial number of studies on subarachnoid hemorrhage-induced cerebral vasospasm have been conducted. They used various species and various methods of inducing experimental subarachnoid hemorrhage such as intracisternal administration of blood (12,19,30,38,39,(43)(44)(45)(46), endovascularly (5,11,22,28,38,44,47) or extravascularly (4,20) puncturing the artery, and blood clot placement around the artery (15). It can be said that existing subarachnoid hemorrhage models of large animals, such as primates and canines, are the preferred models for cerebral vasospasm (31); however, these preferred models are high in cost and often limited in availability due to the difficulties involved in extensive surgery and handling of the subjects when inducing subarachnoid hemorrhage.…”
mentioning
confidence: 99%
See 1 more Smart Citation